Students’ Perceptions of Learning Vocabulary Through Quizizz Word Formation Games: A Qualitative Case Study at Senior High School - Sri Ratih Yulianti; Ina Daril Hanna; Arisandi Setiyawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This qualitative case study explores students' perceptions and learning experiences in using Quizizz word formation games to learn vocabulary at MAN 1 Pamekasan. Thirty eleventh-grade students participated in two Quizizz sessions (Basic and Advanced levels) covering prefixes and suffixes. Data were collected through classroom observations, student worksheets, and semi-structured interviews with fifteen purposively selected students. The findings reveal that students perceived Quizizz as enjoyable, engaging, and more effective than conventional methods. Students particularly favored the leaderboard and avatar features, while the timer was reported as a source of anxiety for the majority of students. Students demonstrated improved morphological awareness through repeated analysis of prefixes, suffixes, and root words, particularly in their ability to analyze complex words using a word-breaking strategy (identifying the root word before analyzing affixes). The instant feedback feature helped students learn from mistakes immediately. This research contributes to the understanding of morphology-based vocabulary learning through digital game-based platforms and provides practical insights for teachers seeking innovative strategies to enhance student engagement and vocabulary mastery.